Rapid autophagic regression of the milk gland during involution is critical for maximizing tsetse viviparous reproductive output. - Joshua B Benoit; Veronika Michalkova; Elise M Didion; Yanyu Xiao; Aaron A Baumann; Geoffrey M Attardo; Serap Aksoy (Public Library of Science (PLoS), 2018)
Tsetse flies are important vectors of human and animal trypanosomiasis. Ability to reduce tsetse populations is an effective means of disease control. Lactation is an essential component of tsetse's viviparous reproductive physiology and requires a dramatic increase in the expression and synthesis of milk proteins by the milk gland organ in order to nurture larval growth. In between each gonotrophic cycle, tsetse ceases milk production and milk gland tubules undergo a nearly two-fold reduction in width (involution). In this study, we examined the role autophagy plays during tsetse fly milk gland involution and reproductive output. Autophagy genes show elevated expression in tissues associated with lactation, immediately before or within two hours post-parturition, and decline at 24-48h post-parturition. This expression pattern is inversely correlated with that of the milk gland proteins (lactation-specific protein coding genes) and the autophagy inhibitor fk506-bp1. Increased expression of Drosophila inhibitor of apoptosis 1, diap1, was also observed in the milk gland during involution, when it likely prevents apoptosis of milk gland cells. RNAi-mediated knockdown of autophagy related gene 8a (atg8a) prevented rapid milk gland autophagy during involution, prolonging gestation, and reducing fecundity in the subsequent gonotrophic cycle. The resultant inhibition of autophagy reduced the recovery of stored lipids during the dry (non-lactating) periods by 15-20%. Ecdysone application, similar to levels that occur immediately before birth, induced autophagy, and increased milk gland involution even before abortion. This suggests that the ecdysteroid peak immediately preceding parturition likely triggers milk gland autophagy. Population modeling reveals that a delay in involution would yield a negative population growth rate. This study indicates that milk gland autophagy during involution is critical to restore nutrient reserves and allow efficient transition between pregnancy cycles. Targeting post-birth phases of reproduction could be utilized as a novel mechanism to suppress tsetse populations and reduce trypanosomiasis.